Compare the Mean Cuff Pressure in Endotracheal Tube Cuff Filled with Air vs Saline in Patients Undergoing Surgery under GA - Hassan Raza, Adnan Bashir, Hamza Waheed, Qaiser Nawaz, Muhammad Arsalan Aftab, Afshan Nisar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Securing and maintaining airway and ventilating the patients by placement of endotracheal1tube is common practice in the operation1theater for delivery of general anesthesia and in the critical care settings. The primary role of endotracheal tube (ETT) cuff’s primary role is to seal the airway, preventing leaks and pharyngeal contents aspiration into the trachea1during ventilation. Aim: To compare the mean cuff pressure in endotracheal1tube cuff filled with air vs saline in patients undergoing surgery under general anesthesia. Study Design: Randomized control trail Place and Duration of Study: Department of Anesthesia, National Hospital, Lahore from 1st July 2016 to 31st December 2016. Methodology: One hundred patients undergoing surgery under general anesthesia were enrolled. They were divided into two groups and each group comprised equal number of patients. In group A, endotracheal tube was inserted with air filled cuff while in group B, endotracheal tube was inserted by using 0.9%saline solution. On follow-up outcome was noted. Results: The average age of the air filled cuff was 38.24±12.22 years and in saline filled cuff group was 39.68±13.79 years. Insignificant (p=0.269) difference statistically was found between the groups with cuff pressure at baseline of the patients and insignificant difference was noted at baseline. Conclusion: The mean cuff pressure in ETT was significantly less with saline than air filled cuff in patients undergoing surgery under general anesthesia.